A Qualitative Evaluation of CSA Options in Mixed Crop-Livestock Systems in Developing Countries - Thornton, Philip K.; Rosenstock, Todd S.; Förch, Wiebke; Lamanna, Christine; Bell, Patrick; Henderson, Benjamin B.; Herrero, Mario (Springer, 2018)
The mixed crop-livestock systems of the developing world will become increasingly important for meeting the food security challenges of the coming decades. The synergies and trade-offs between food security, adaptation, and mitigation objectives are not well studied, however. Comprehensive evaluations of the costs and benefits, and the synergies and trade-offs, of different options in developing- country mixed systems do not exist as yet. Here we summarise what we know about the climate smartness of different alternatives in the mixed crop- livestock systems in developing countries, based on published literature supplemented by a survey of experts. We discuss constraints to the uptake of different interventions and the potential for their adoption, and highlight some of the technical and policy implications of current knowledge and knowledge gaps.